MEKANISME ASEAN REGIONAL FORUM DALAM MENANGANI ISU TERORISME REGIONAL - Busthomi, M. Ali (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
This article aims to describe the mechanism of ARF forum as ASEAN's efforts in tackling regional terrorism. The type of article is the content analysis. The objectof this article are the various agreements in ASEAN Regional Forum, as the step in tackling the issue of regional terrorism. The findings showed that the agreement of the classification of terrorist movements as transnational crime, the signing of the agreement in the field of information exchange and establishment of communication procedures among Indonesia, Malaysia and the Philippines. the agreements and commitments for the financing of terrorist activities against the freezing of terrorist assets in banks of ARF member countries, and exchange of information and documents relating to the terrorist groups of financial traffic.